Aplikasi Mesin Pemasak Minuman Rempah Jahe (Zingiber officinale) Dengan Pengaduk Otomatis di UKM Polanmadu - Choiroel Anam; Nindyah Widyamurti; Danar Praseptiangga; Anastriyani Yulviatun; Dwi Aries Himawanto (PRIMA: Journal of Community Empowering and Services, 2021)
Cooking Machine Application of Ginger Drink (Zingiber officinale) with Automatic Stirrer at UKM Polanmadu. The trend of instant spice drinks that function to maintain the body’s immunity is growing rapidly in the era of the Covid-19 pandemic. Ginger, which is a spice with various benefits, has made many Small and Medium Enterprises (SMEs) industry players take advantage of this potential. One of them is the instant spice drink SME industry player "Polanmadu" which produces natural instant spice drinks. The processing of instant spice drinks is still done conventionally, making Polanmadu SMEs unable to reach consumer demands. The purpose of these activities was to the introduction of appropriate technology in the production of instant spice drinks to produce products with more guaranteed quality and able to generate additional income for partners. The application of the cooking machine is useful so that the stirring process which has been going on for 3 hours conventionally using human power is replaced with electric power so that it is more efficient and profitable. The implementation begins with identification, planning, assembling tools, testing tools, and introducing tools to the spice instant drink production unit. The result showed that the introduction of a spice instant drink cooking machine can produce 20% more crystal ginger extract, automatic stirring while at the same time speeding up the formation of crystals from 3 hours to 2.5 hours, and the product crystal size is more homogenous and an increase in profit of Rp906,000-/day. Overall, the introduction of this spice-cooking machine makes the productivity of SMEs for instant spice drinks increase in quality and quantity.